Tolerance and acceptance of hepatic venous pressure gradient measurement in cirrhosis (CHESS1904): An international multicenter study. Issue 1 (31st May 2022) - Sun, Jun‐Hui; Zhao, He; Zhang, Haijun; Li, Lei; Örmeci, Necati; Yu, Zi‐Niu; Li, Xun; Li, Shuangxi; Yang, Xujun; Wei, Huaping; Zhu, Xiaoliang; Zhang, Zhengcong; et al.
Abstract: Aim: To determine the tolerance and acceptance of hepatic venous pressure gradient (HVPG) measurements in patients with liver cirrhosis. Methods: This prospective international multicenter study included 271 patients with cirrhosis who were scheduled to undergo HVPG measurement between October 2019 and June 2020. Data related to the tolerance and acceptance of HVPG measurements were collected using descriptive questionnaires. Results: HVPG measurements were technically successful in all 271 patients, with 141 (52.0%) undergoing HVPG measurement alone. The complication rate was 0.4%. Postoperative pain was significantly lower than preoperative expected pain ( p  < 0.001) and intraoperative pain ( p  < 0.001), and intraoperative pain was also significantly lower than preoperative expected pain ( p  = 0.036). No, mild, moderate, severe, and intolerable discomfort scores were reported by 36.9%, 44.6%, 11.1%, 6.3%, and 0.4% of these patients, respectively, during HVPG measurement and by 54.6% 32.5%, 11.4%, 1.5%, and 0%, respectively, after HVPG measurement. Of these patients, 39.5% had little understanding and 10% had no understanding of the value of HVPG measurement, with 35.1% and 4.1% regarding HVPG measurements as being of little or no help, respectively. Most patients reported that they would definitely (15.5%), probably (46.9%), or possibly (29.9%) choose to undergo additional HVPG measurements again, and 62.7% regarded the cost of the procedure as acceptable. Conclusion: HVPG measurement was safe and well‐tolerated in patients with cirrhosis, but patient education and communication are warranted to improve the acceptance of this procedure. Key points: Significant findings of the study : This prospective multicenter study showed that HVPG measurement was well‐tolerated in patients with cirrhosis, but the acceptance of HVPG measurement was not as high as expected. What this study adds : Although HVPG measurement was safe and well‐tolerated in patients with cirrhosis, more in‐depth patient education and communication are warranted to improve the acceptance of the procedure. Abstract : HVPG measurement was safe and well‐tolerated in cirrhosis, however, patient‐education and communication were warranted to improve the acceptance of the procedure.